Factors Associated with Stunting in Toddlers in Indonesia: Analysis of the 2024 Indonesian Nutrition Status Survey (SSGI) for Evidence-Based Nutrition Policy - Leka Lutpiatina; Muhammad Rizal (Tropical Health and Medical Research, 2026)
Stunting remains a major public health challenge in Indonesia and is associated with multiple biological, maternal, social, and environmental factors. This study aimed to identify factors associated with stunting among toddlers in Indonesia and characterize geographic variation in stunting prevalence across provinces using the 2024 Indonesian Nutrition Status Survey (SSGI). This cross-sectional observational study used data from 298,970 toddlers across 38 provinces and 510 districts/cities. Weighted multivariable logistic regression with province as a fixed effect was used to estimate adjusted odds ratios (AORs), complemented by Global Moran’s I, Local Indicators of Spatial Association (LISA), and quantile mapping to assess geographic distribution and spatial autocorrelation. The prevalence of stunting was 22.7%. Males (OR 1.11), children living in rural areas (OR 1.32), those aged 24–35 months (OR 1.29), those with low birth weight (OR 2.08), and those born prematurely (OR 1.34) had higher odds of stunting. Lower parental education, iron supplementation of <90 tablets, incomplete antenatal care, maternal anaemia, chronic energy deficiency, inadequate sanitation (OR 1.44), inadequate drinking water (OR 1.45), and high residential density (OR 1.38) were also significantly associated with stunting (p < 0.05). Significant differences in adjusted odds were observed across provinces (?² = 618.977; p < 0.001), with the highest AORs in Highlands Papua (5.82; 95% CI: 3.55–9.56) and East Nusa Tenggara (4.69; 95% CI: 3.70–5.95), compared with Bali as the reference province. Spatial analysis demonstrated significant positive spatial autocorrelation (Moran’s I = 0.3634; Z = 2.7271; p = 0.01), with high-prevalence clustering in the eastern region. Stunting was associated with multiple individual, household, and environmental factors and showed significant geographic clustering across Indonesian provinces. Evidence-based, geographically targeted strategies should prioritise interventions from pregnancy through the first two years of life, nutritional literacy, immunisation coverage, sanitation, drinking water, and healthy housing, particularly in high–high spatial clusters.